PENGUATAN KELEMBAGAAN DAN MANAJEMEN KOPERASI KARYAWAN SEBAGAI UPAYA PENINGKATAN KESEJAHTERAAN ANGGOTA - Oriza Sativa; Dyah Ayu Sukmawati; Anisah Fitri; Ida Ayu Nuh Kartini (Adiba Aisha Amira, 2026)
This study aims to analyze the strengthening of institutional and management aspects of employee cooperatives as an effort to improve members’ welfare in a sustainable manner. Employee cooperatives play a strategic role in supporting the economic and social welfare of workers; however, in practice, they still face various challenges, particularly in institutional capacity and management practices. This research employs a qualitative approach with a descriptive research design. The data used are secondary data obtained through a literature review of books, scientific journals, previous studies, and regulations related to cooperatives. The results indicate that although employee cooperatives have established institutional structures in accordance with existing regulations, their implementation has not been optimal. Low member participation, limited managerial and supervisory capacity, and weak application of good cooperative governance are the main obstacles. Therefore, strengthening institutional capacity and implementing professional, transparent, and participatory management are essential to enhance both economic and social benefits and to improve members’ welfare sustainably